The Pros and Cons of Lengger Lanang in Banyumas Society - Mohamad Zaki Mubarok; Ayu Restu Putri; Rinaningsih; Tania Selasi Amara Azizah; Laila Khoirunnisa; Puspitasari, Elis (Jurnal Seni Tari, 2024)
This research examines the pros and cons and the existence of Lengger Lanang dance in Banyumas society today. Lengger Lanang is a traditional dance in which male dancers dress as women, which has its roots in the Dutch colonial period. Using descriptive-analytical qualitative method with snowball sampling technique, this research conducted interviews with dance studio owners and lengger house managers. The results showed that there are pro and contra views towards Lengger Lanang in the community. The pros see it as a cultural heritage that should be preserved, while the cons are concerned about the moral and religious aspects. This controversy impacts the existence of Lengger Lanang, with a decline in preservation and training efforts. To address the controversy, strategies such as providing understanding to young dancers and efforts to embrace dancers experiencing gender identity change are proposed. This research reveals the complexity of gender and sexuality issues in the context of traditional arts, as well as the tension between cultural preservation and changing social values. Despite the challenges, there are still efforts to preserve and adapt these dances to remain relevant in contemporary society.